Efektivitas program kemandirian harian terstruktur terhadap peningkatan keterampilan merawat diri Anak Hambatan Intelektual - Hardiyanti Purna Pratiwi; Nabila Ramadhani; Briani Wikan Nareswara; Ernisa Purwandari (Literal: Disability Studies Journal, 2025)
This study aims to examine the effectiveness of a structured daily independence program in improving self-care skills among students with intellectual disabilities living in the dormitory of SLB Negeri Pembina Yogyakarta. The research employed a quantitative approach using a quasi-experimental design with a one group pretest-posttest. The participants were 10 students with intellectual disabilities aged 12–17 years. The research instrument was developed based on the adaptive behavior domains of the American Association on Intellectual and Developmental Disabilities (AAIDD), focusing on five aspects of self-care skills: mopping the floor, sweeping the floor, washing hair, ironing clothes, and doing laundry. Data were collected through observation, tests, and documentation, and analyzed using the Wilcoxon Signed Rank Test at a significance level of 0.05. The findings revealed a significant improvement in all aspects of self-care skills after the implementation of the structured daily independence program. This was evidenced by the calculated Thitung values being greater than the Ttabel values, and Zhitung > Ztabel (1.96) for all tested skills. Therefore, the structured daily independence program was proven effective in enhancing the independence of students with intellectual disabilities in the dormitory.